Antifungal properties of organic extracts of eight Cistus L. species against postharvest citrus sour rot. (1st January 2016) - Karim, H.; Boubaker, H.; Askarne, L.; Talibi, I.; Msanda, F.; Boudyach, E.H.; Saadi, B.; Ait Ben Aoumar, A.
Abstract: The effectiveness of methanol and chloroform extracts of eight Cistaceae species to control citrus sour rot decay, caused by Geotrichum citri‐aurantii, was investigated in both in vitro and in vivo conditions. Methanol extracts of these plant species exhibited more interesting activity against G. citri‐aurantii, in both in vitro and in vivo conditions, compared with chloroforme extracts. Under in vitro trials, obtained results showed that methanol extracts of all tested plants revealed a highest significant antifungal activity with inhibition zones that ranged between 12·33 and 16·33 mm in diameter. All tested methanol extracts totally inhibited spore germination when tested at 10 mg ml −1 . Incidence of sour rot was significantly lowered to 11·11% when fruits were treated with Cistus populifolius and Cistus ladanifer methanol extracts compared with 100% in the control. The disease severity was lowered to 5·19% and 6·04% when fruits were treated with the same methanol extracts respectively. Significance and Impact of the Study: The methanol Cistus extracts had sufficient antifungal activities in vitro and in vivo against G. citri‐aurantii to consider its use in the citrus industry after it has been tested under production and natural infection conditions. Such natural products therefore represent a viable alternative approaches for sour rot postharvest management of citrus.